The consequence of inadequate design on building maintenance potential - Eusuf, Muhammad Abu; Ibrahim, Mansor; Abdul Rashid, Khairuddin (2010)
The purpose of this study is to categorize the defects and faults during the design stage that affect building maintenance potential in Malaysia. To perform this study it is essentially needs to organize field survey among the sustainable users such as constructors, builders, architectural/ engineering firms and owners from the east Malaysia. The survey included probable defects and the respondents were asked to indicate their degree of importance. The defects are grouped into several sets. The level of importance of the defects and the sets are measured and ranked by their rigorousness index for sustainable users. The aim of the present investigation is also to develop an advanced design model for the behaviour of structural components into account of the soil-structure-interaction. The results of tests on the performance of structural materials are presented. The experimental results indicate that the failure plane is observed on flat slabs, and the beam.